Flyover Country - Stan Herd (Oz, 1997)
A Kansas farm child discovers the world one small intimate detail at a time. When encoumered for the first time, a sparrow is as fascinating as the universe. Without majestic moumains or postcard sea coasts for comparison we are forced to focus on subtle detail.